Ideologi dalam slogan aksi demonstrasi mahasiswa terhadap revisi UU Pilkada: Analisis wacana kritis Norman Fairclough - Efaphras Cinta Tyas Gusti; Eti Setiawati (Diglosia, 2025)
This research aims to discuss the ideology of discourse that appears in the slogans of student demonstrations. The research method used is descriptive qualitative. Data in the form of slogan discourse was taken from social media X. The data analysis technique uses Norman Fairclough's critical discourse analysis approach, which focuses on three dimensions: the text dimension, discourse practice, and sociocultural. The results showed that in the text dimension, a form of clause representation was found in the form of using metaphors as an affirmation of meaning, such as dikremasi, tukang kayu, disandera, and mengebiri. Religious vocabulary that shows moral values, such as halal, Yesus, and azab. The representation in the combination of clauses illustrates the coherence shown by the form of elaboration marked by the conjunctions: yang and tanpa. The analysis of the discourse practice dimension shows that the author of the slogan, namely students, plays a role as a driver of anti-political dynasty ideology. In the sociocultural dimension, a situational level was found where the slogan discourse was influenced by the condition of the community that was disturbed by the issue of political dynasties ahead of the 2024 regional head elections.